2020
DOI: 10.1111/jcmm.16209
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic stellate cells specific liposomes with the Toll‐like receptor 4 shRNA attenuates liver fibrosis

Abstract: Liver fibrosis is a dynamic and potentially reversible wound-healing process that maintains liver integrity and signifies an early stage of liver cirrhosis. 1 The aetiological factors of liver fibrosis include infections (hepatitis virus and schistosome), fatty liver disease (alcoholic and non-alcoholic), cholestasis and autoimmune liver disorders. 2 The typical pathological characteristic of liver fibrosis includes inflammatory cell infiltration and fibrogenesis, which occurs because of chronic liver injury. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Excessive ROS produced by diverse oxidative biochemical enzymes disturbs the normal action of liver-specific cells and probably engages in liver fibrosis occurrence. [44] Moreover, ROS generation is implicated in HSC activation, [45,46] revealing its importance in liver fibrosis. We found that ROS level was elevated in TGF-β1-induced LX-2 cells, whereas reduced after Tβ4 overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive ROS produced by diverse oxidative biochemical enzymes disturbs the normal action of liver-specific cells and probably engages in liver fibrosis occurrence. [44] Moreover, ROS generation is implicated in HSC activation, [45,46] revealing its importance in liver fibrosis. We found that ROS level was elevated in TGF-β1-induced LX-2 cells, whereas reduced after Tβ4 overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…Recent developments in terms of delivery of RA and RAR-selective retinoids include delivery in nanoparticles (149)(150)(151) and delivery in liposomes (152,153). Interestingly, the properties of VA itself have been used to enhance specific delivery of cationic liposomes containing short hairpin RNAs to stellate cells in the liver (154). An excellent review on the formulation and delivery of retinoids was recently published (155).…”
Section: Challenges Of Developing Synthetic Retinoids Into Drugsmentioning
confidence: 99%
“…Fully activated HSCs release and upregulate expression of TIMP-1 and TIMP-2, which inactivate MMPs through proteolytic cleavage [ 43 , 45 , 48 ]. Targeting activated HSCs in vivo decreased the expression of TIMP-1 and TIMP-2 and resulted in attenuated liver fibrosis [ 49 ]. Impairment of HSCs activation in mice downregulated TIMP-1 and diminished alcohol-induced steatohepatitis [ 50 ].…”
Section: The Role Of Ahscs In Hccmentioning
confidence: 99%